2018
DOI: 10.1186/s10020-018-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Different sulfonylureas induce the apoptosis of proximal tubular epithelial cell differently via closing KATP channel

Abstract: BackgroundSulfonylureas (SUs) are widely prescribed for the treatment of type 2 diabetes (T2DM). Sulfonylurea receptors (SURs) are their main functional receptors. These receptors are also found in kidney, especially the tubular cells. However, the effects of SUs on renal proximal tubular epithelial cells (PTECs) were unclear.MethodsThree commonly used SUs were included in this study to investigate if different SUs have different effects on the apoptosis of PTECs. HK-2 cells were exposed to SUs for 24 h prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…Recently it was shown that death receptors can be established in a soluble form in the bloodstream (24). Levels of serum (TNF-R1) concentration (pg/mL) for studied groups showed that there were not significant differences between patients group when compared with control group , so the result of the current study showed that using of Sulfonylureas therapy may reduce TNF-R1 concentration .This finding was consistent with literature data which know that the levels of serum TNF and its receptors were significantly decreased in diabetic patients with Sulfonylureas treatment (25). The results of TRAIL-R2 concentration (pg/mL) showed elevated significant difference between patients groups (P<0.0001), when compared to control groups.…”
Section: Resultssupporting
confidence: 90%
“…Recently it was shown that death receptors can be established in a soluble form in the bloodstream (24). Levels of serum (TNF-R1) concentration (pg/mL) for studied groups showed that there were not significant differences between patients group when compared with control group , so the result of the current study showed that using of Sulfonylureas therapy may reduce TNF-R1 concentration .This finding was consistent with literature data which know that the levels of serum TNF and its receptors were significantly decreased in diabetic patients with Sulfonylureas treatment (25). The results of TRAIL-R2 concentration (pg/mL) showed elevated significant difference between patients groups (P<0.0001), when compared to control groups.…”
Section: Resultssupporting
confidence: 90%
“…Different types of sulfonylureas are widely used to treat type 2 diabetes mellitus (T2DM) [ 24 , 25 ]. Hence, we tested the effects of tolbutamide, chlorpropamide, glipizide, glibenclamide and glimepiride, all of which are sulfonylureas, for their abilities to stimulate insulin secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al 71 . reported that different sulfonylurea compounds could mediate PTEC apoptosis by closing the K ATP channel at different binding selectivity and reversibility.…”
Section: Apoptosis Of Renal Tubular Cells In Dkdmentioning
confidence: 99%
“…69 Additionally, Mou et al revealed that the apoptosis of tubules was significantly decreased by a combination of prostaglandin E1 and angiotensin-converting enzyme (ACE) inhibitors, which showcased the remarkable protective effect prostaglandin E1 and ACE inhibitors have on renal function in DKD. 70 Zhang et al 71 reported that different sulfonylurea compounds could mediate PTEC apoptosis by closing the K ATP channel at different binding selectivity and reversibility. A therapeutic effect of gliclazide on the inhibition of PTEC apoptosis was also observed, which benefited the preservation of functional PTEC mass.…”
Section: Uric Acidmentioning
confidence: 99%